Model of Library Management and Service in Islamic Educational Institutions: “Kebun Buku” Library as Best Practice - Suci Tiandari Agustina K.; Suwandi (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
This study aims to describe and explain the management model and services of the school library, as well as what factors are the support and obstacles in the management and services of the library. The research was conducted at the library of SMANU 1 Gresik. A qualitative approach is used in this research and its type is a case study. Data collection was carried out by interview, observation and documentation. The data analysis was carried out in three stages, namely data reduction, data presentation, and verification. Meanwhile, related to testing the validity of the data, researchers used the triangulation technique of data sources. The results of this study indicate that: Firstly, library management at SMANU 1 Gresik is carried out in several aspects, including: human resources, place resources (infrastructure), library material sources (references), and time resources. Secondly, the services provided by the library to customers or users include: circulation services, reference services, documentation services, learning guidance services (literacy), storytelling services, subject teacher consultation services, and services to Public. Thirdly, the supporting factors for library management and services are the support from the leadership (school principal) and adequate library facilities. Meanwhile, the inhibiting factors are the budget, which has been increased again, and the human resources (users) of services who are still less disciplined. The research results are expected to be examples of best practices for educational institutions, especially Islamic educational institutions. Keywords: library management, library services,